Legal Review of Children Born Out of Wedlock Based on Islamic Inheritance Law and Civil Law - Nurfitryani Siregar; Nur Hakima Akhirani Nasution (PT Inovasi Pratama Internasional, 2023)
In the context of Islamic law, the division of inheritance is one of the studies in Islam which in science is discussed specifically in the Fiqh of Mawaris. This is none other than to prevent disputes between family members related to the inheritance of family members who have died. In essence, the position of the child is not only a blessing but also a mandate from Allah SWT. In the view of Islam, child protection has a fundamental meaning, namely as the basis of values ​​and paradigms for changing the fate of children. In civil law, marriage is the basis for the realization of family ties and this gives birth to rights and obligations among those who are included in the family environment. Children born from legal marriages and automatically have a civil relationship with their father, this is stated in Article 250 of the Civil Code (hereinafter referred to as the Civil Code) which states that every child born or raised during marriage, obtains the husband as his father. The position of children in inheritance rights is also explained in the Civil Code in Article 852 which states that